Efektivitas Pengembangan Modul Pembelajaran Berbasis Project Based Learning selama Pandemi pada Matapelajaran TIK di Sekolah Menengah Pertama Negeri - Khairani, Eka; Maksum, Hasan; Rizal, Fahmi; Adri, Muhammad (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
Innovation and development of the learning process especially during pandemic covid-19, which is a learning process delivered by online techtechnologynologi. support knowledge o the student, need an effective of student on the online student. can create new ideas in the delivery of education An interesting and independent learning requires a media that can stimulate students' interest and participation in the learning, not only dwell with inanimate objects without any direct interaction with the teacher. This study aims to measure how of validity and effectivity & Practicality of PjBL Modul. This book was implemented on SMP Negeri 9 Padang and finally, from evaluation, we get validity, practically, and effectiveness of media. The purpose of this research is to produce a Project-Based Learning Module an effective Modul on ICT subjects based on PjBL Modul. which is designed as an alternative learning media. The method in this study uses the ADDIE Model with development procedures, namely the Analysis, Definition, Design, Implementation, and Evaluation stages. The results obtained from this development research: The validity of the media was declared valid with a value of 89.35 by media experts and 88.25 by material experts. The practicality of the media from the lecturer's response got a score of 85.42% (practical) and 84.11 (practical) from the teacher's response. The effectiveness of the media in the effectiveness trial, 80% of students got a score of 75 (classical effectiveness). And in terms of Gain Score, it gets a value of 0.44% (medium), so the Project-Based Learning Module is declared effective in improving learning outcomes. Based on the findings of this study, it was concluded that the Project-Based Learning Module was declared valid, practical, and effective to be used as a learning medium in ICT on SMP Negeri 9 Padang.